Game of Thrones. The complete fifth season [videorecording (Blu-Ray)] - Benioff, David; Weiss, D. B. (Game of thrones (TV series), 2016)
"This season begins with a power vacuum that protagonists across Westeros and Essos look to fill. At Castle Black, Jon Snow struggles to balance the demands of the Night's Watch with those of newly-arrived Stannis Baratheon, who styles himself the rightful king of Westeros. Meanwhile, Cersei scrambles to hold on to power in King's Landing amidst the Tyrells and the rise of a religious group led by the enigmatic High Sparrow, while Jamie embarks on a secret mission. Across the Narrow Sea, Arya seeks an old friend while a fugitive Tyrion finds a new cause. And as danger mounts in Meereen, Daenerys Targaryen finds that her tenuous hold on the city requires some hard sacrifices."--Container.